Luminal sulfide and large intestine mucosa: friend or foe - Blachier, François; Davila, Anne-Marie; Mimoun, Sabria; Benetti, Pierre-Henri; Atanasiu, Calina; Andriamihaja, Mireille; Benamouzig, Robert; Bouillaud, Frédéric; Tomé, Daniel (Amino acids, 2010)
Hydrogen sulfide (H₂S) is present in the lumen of the human large intestine at millimolar concentrations. However, the concentration of free (unbound) sulfide is in the micromolar range due to a large capacity of fecal components to bind the sulfide. H₂S can be produced by the intestinal microbiota from alimentary and endogenous sulfur-containing compounds including amino acids. At excessive concentration, H₂S is known to severely inhibit cytochrome c oxidase, the terminal oxidase of the mitochondrial electron transport chain, and thus mitochondrial oxygen (O₂) consumption. However, the concept that sulfide is simply a metabolic troublemaker toward colonic epithelial cells has been challenged by the discovery that micromolar concentration of H₂S is able to increase the cell respiration and to energize mitochondria allowing these cells to detoxify and to recover energy from luminal sulfide. The main product of H₂S metabolism by the colonic mucosa is thiosulfate. The enzymatic activities involved in sulfide oxidation by the colonic epithelial cells appear to be sulfide quinone oxidoreductase considered as the first and rate-limiting step followed presumably by the action of sulfur dioxygenase and rhodanese. From clinical studies with human volunteers and experimental works with rodents, it appears that H₂S can exert mostly pro- but also anti-inflammatory effects on the colonic mucosa. From the available data, it is tempting to propose that imbalance between the luminal concentration of free sulfide and the capacity of colonic epithelial cells to metabolize this compound will result in an impairment of the colonic epithelial cell O₂ consumption with consequences on the process of mucosal inflammation. In addition, endogenously produced sulfide is emerging as a prosecretory neuromodulator and as a relaxant agent toward the intestinal contractibility. Lastly, sulfide has been recently described as an agent involved in nociception in the large intestine although, depending on the experimental design, both pro- and anti-nociceptive effects have been reported.